2020
DOI: 10.3389/fphar.2020.00124
|View full text |Cite
|
Sign up to set email alerts
|

From Cannabis sativa to Cannabidiol: Promising Therapeutic Candidate for the Treatment of Neurodegenerative Diseases

Abstract: Cannabis sativa, commonly known as marijuana, contains a pool of secondary plant metabolites with therapeutic effects. Besides D9-tetrahydrocannabinol that is the principal psychoactive constituent of Cannabis, cannabidiol (CBD) is the most abundant nonpsychoactive phytocannabinoid and may represent a prototype for antiinflammatory drug development for human pathologies where both the inflammation and oxidative stress (OS) play an important role to their etiology and progression. To this regard, Alzheimer's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 90 publications
1
85
0
12
Order By: Relevance
“…Cannabinoids are of significant interest recently, especially non-psychoactive phytocannabinoids such as CBD, as the market expanded dramatically [ 11 ]. Recently, there has been a flash of research articles on CBD effects on human health [ 9 , 11 , 47 ]. Previous research has shown that CBD has anti-epileptic, anti-inflammatory, and anti-psychotic properties [ 48 ] and against neurodegenerative diseases [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabinoids are of significant interest recently, especially non-psychoactive phytocannabinoids such as CBD, as the market expanded dramatically [ 11 ]. Recently, there has been a flash of research articles on CBD effects on human health [ 9 , 11 , 47 ]. Previous research has shown that CBD has anti-epileptic, anti-inflammatory, and anti-psychotic properties [ 48 ] and against neurodegenerative diseases [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been a flash of research articles on CBD effects on human health [ 9 , 11 , 47 ]. Previous research has shown that CBD has anti-epileptic, anti-inflammatory, and anti-psychotic properties [ 48 ] and against neurodegenerative diseases [ 9 ]. A recent review summarized the various molecular pathways that cause positive effects of CBD, especially with respect to the major neurodegenerative disorders [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a broad therapeutic potential resulting from its anti-inflammatory, antioxidant, anticonvulsant, antipsychotic, anxiolytic and antiproliferative properties. It is approved by the US Food and Drug Administration for the treatment of resistant epilepsy, and it is indicated in the therapy of neuropathic pain in multiple sclerosis and other diseases [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds seem to play a substantial role as antioxidant and anti-inflammatory properties and can be beneficial in the therapeutic approach of several diseases such as Alzheimer's disease, Parkinson's disease, neuropathic pain, chronic pain, anxiety, schizophrenia, and cancer. IBD patients can also benefit from the use of this plant or its derivatives [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%